Pertumbuhan UMKM Pasca Pandemi Covid 19 Dengan Menggunakan Media E-Commerce - Ninda Rachmawati; Anudiyan Amir Mas’ud (JOURNAL KOPERASI DAN MANAJEMEN, 2023)
Purpose – The purpose of this study was to determine what actions or tactics MSMEs may take to sustain their operations in the face of COVID 19. In particular when pandemics strike, this study will explain how MSMEs use measures to remain in operation and adapt more quickly to market shifts. Design/methodology/approach – The topic and area of research interest are described in this study using a qualitative methodology. Methods of qualitative research are those that rely on qualitative data rather than a statistical foundation. Findings – Because so many people are now buying online, the suggested survival strategy for MSMEs to be able to retain their business is to (1) earn sales through e-commerce. (2) Using digital technology for product promotion (digital marketing) in order to reach more customers (3) Enhance the standard of both the type and caliber of the service as well as the product. Research limitations/implications – Because it employs descriptive and qualitative approaches, this study includes more subjective informants, who run a significant risk of lowering the objectivity of the research findings. The researcher’s personality will influence the research’s findings; hence, when you meet other researchers with various personalities, the findings may change. Originality/value – E-commerce has been shown in studies (Hardilawati, 2019; Setyorini et al., 2019) to positively and significantly affect marketing effectiveness and MSME revenue. This study discovered that e-commerce sales were widespread. (2) Product promotion via digital marketing (3) Improving the caliber of the product and service